For any non-zero a and b, that satisfy |ab| = ab and |a| = -a, |b – 4| + |ab – b| = A. ab – 4 B. 2b – ab – 4 C. ab + 4 D. ab – 2b + 4 E. 4 – ab
(D) We know that |a| = -a. Since an absolute value must be positive, then -a > 0, which results in a < 0. Considering this fact together with |ab| = ab we reason out that b < 0, because ab > 0 and a < 0. So (b – 4) < 0 as well. Therefore |b – 4|= 4 – b b < 0 and a – 1 < 0 so b(a – 1) > 0 |ab – b| = |b(a – 1)| = b(a – 1).
Summarizing all of the above reasoning we get |b – 4| + |ab – b| = -b + 4 + ab – b = ab – 2b + 4
If you are unable to make sense of the algebra, you can plug in negative numbers for the two values in each of the answer choices to get choice (D). ---------- Explanation is not clear at all.
Users browsing this forum: Yahoo [Bot] and 1 guest
You cannot post new topics in this forum You cannot reply to topics in this forum You cannot edit your posts in this forum You cannot delete your posts in this forum You cannot post attachments in this forum
GMAT(TM) and GMAT CAT (TM) are registered trademarks of the Graduate Management Admission Council(TM). The Graduate Management Admission Council(TM) does not endorse, nor is affiliated in any way with the owner or any content of this site.